Sensory quality of meat from lambs fed on different diets - A. Vicenti; M. Morgante; R. Valusso; E. Piasentier; M. Ragni (Italian Journal of Animal Science, 2010)
The whole seed of sweet lupin var. Multitalia with a protein content higher than 35% and a low content in alkaloids constitutes a good protein source alternative to soybean meal, today deriving for more than 60% from OGM (Genetically Modified Organisms) cultivation. Moreover, the poor national production and the cost of feeds for animals forces the livestock compartment to utilize alternative biomasses the availability of which highly depends on from the environment and the season.